AGRICULTURAL ADVISORY AND ITS ROLE IN AGRITOURISM ACTIVITY DEVELOPMENT - Agnieszka Brelik (Acta Scientiarum Polonorum. Oeconomia, 2010)
Development of economic activity in rural areas is one of the main tasks of agricultural advisory centres. They stimulate agricultural development by indicating some local problems and helping with solving them. Agricultural advisors organize and lead trainings, demonstrations, expositions, presentations, etc. that encourage farmers to start their own agritourism activity. Development of this form of tourism mainly depends on local authorities and organizations of the region. The main aim of the research was to present the role of agricultural advisory centres in developing agritourism activity. Moreover, the author tried to find answer for the question: may agriculture advisory centres be able to support non-agricultural activity in rural areas?